2015
DOI: 10.14309/crj.2014.84
|View full text |Cite
|
Sign up to set email alerts
|

Graft-Versus-Host Disease of the Upper Gastrointestinal Tract After an Autologous Stem Cell Transplant

Abstract: Graft-versus-host disease (GVHD) in recipients of autologous stem cell transplantation (SCT) is less common compared to recipients of allogeneic SCT, but its existence has been well documented. Similarly, the diarrheal component of the disease is highlighted when discussing its gastrointestinal (GI) manifestations, with less emphasis given to upper GI symptoms like nausea and vomiting. We present a case illustrating the upper GI tract signs and symptoms of GVHD after autologous SCT, and emphasize that prompt t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…2 The diagnosis is confirmed histologically with apoptotic epithelial cells or crypt cell dropout with lymphocytic infiltrates. 8 Several studies have shown that patients with MM are at a higher risk of developing auto-GVHD compared with other patients undergoing auto-HSCT. 9 Furthermore, it has been suggested that auto-GVHD in MM patients can follow a more severe course and may not respond to steroids as desired.…”
Section: Discussionmentioning
confidence: 99%
“…2 The diagnosis is confirmed histologically with apoptotic epithelial cells or crypt cell dropout with lymphocytic infiltrates. 8 Several studies have shown that patients with MM are at a higher risk of developing auto-GVHD compared with other patients undergoing auto-HSCT. 9 Furthermore, it has been suggested that auto-GVHD in MM patients can follow a more severe course and may not respond to steroids as desired.…”
Section: Discussionmentioning
confidence: 99%
“…13,37 The phenomenon of autologous GVHD has been reported and the syndrome occurs in up to 10% of autograft recipients. 38,39 Moreover, 6% of patients with documented membranous glomerulonephritis after HSCT had undergone autografts. In such cases, it is hypothesised that the pathophysiology underlying the renal injury relates to posttransplantation immune dysregulation resulting in T-and B-cell targeting of podocyte antigens.…”
Section: Discussionmentioning
confidence: 99%
“…In the allogeneic transplant setting, membranous glomerulonephritis has been increasingly considered to be a manifestation of chronic GVHD involving the kidneys 13,37 . The phenomenon of autologous GVHD has been reported and the syndrome occurs in up to 10% of autograft recipients 38,39 . Moreover, 6% of patients with documented membranous glomerulonephritis after HSCT had undergone autografts.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst isolated case reports, Fidler, et al described a case of auto-GVHD with skin and gastrointestinal manifestations in a patient with MM, who ultimately deteriorated and expired despite steroid therapy [5]. Recently, Barbash, et al described a case of spontaneous GI GVHD with predominant upper GI involvement in a patient of multiple myeloma who underwent autologous HSCT [6].…”
Section: Discussionmentioning
confidence: 99%